Contrasted patterns of local adaptation to climate change across the range of an evergreen oak, Quercus aquifolioides. (9th June 2020) - Du, Fang K.; Wang, Tianrui; Wang, Yuyao; Ueno, Saneyoshi; de Lafontaine, Guillaume
Abstract: Long‐lived tree species are genetically differentiated and locally adapted with respect to fitness‐related traits, but the genetic basis of local adaptation remains largely unresolved. Recent advances in population genetics and landscape genomic analyses enable identification of putative adaptive loci and specific selective pressures acting on local adaptation. Here, we sampled 60 evergreen oak ( Quercus aquifolioides ) populations throughout the species' range and pool‐sequenced 587 individuals at drought‐stress candidate genes. We analyzed patterns of genetic diversity and differentiation for 381 single nucleotide polymorphisms (SNPs) from 65 candidate genes and eight microsatellites. Outlier loci were identified by genetic differentiation analysis and genome–environment associations. The response pattern of genetic variation to environmental gradient was assessed by linear isolation‐by‐distance/environment tests, redundancy analysis, and nonlinear methods. SNPs and microsatellites revealed two genetic lineages: Tibet and Hengduan Mountains–Western Sichuan Plateau (HDM‐WSP), with reduced genetic diversity in Tibet lineage. More outlier loci were detected in HDM‐WSP lineage than Tibet lineage. Among these, three SNPs in two genes responded to dry season precipitation in the HDM‐WSP lineage but not in Tibet. By contrast, genetic variation in the Tibet lineage was related to geographic distance instead of the environment. Furthermore, risk of nonadaptedness (RONA) analyses suggested HDM‐WSP lineage will have a better capacity to adapt in the predicted future climate compared with the Tibet lineage. We detected genetic imprints consistent with natural selection and molecular adaptation to drought on the Qinghai–Tibet Plateau (QTP) over a range of long‐lived and widely distributed oak species in a changing environment. Our results suggest that different within‐species adaptation processes occur in species occurring in heterogeneous environments.